Pelatihan Cara Pembuatan Database Untuk Pengarsipan Di Desa Sei Mencirim Sunggal - Aulia Rahmah, Sabrina; Yasir, Amru; Sinaga, Kariaman; Rahman Syahputra, Edy (Jurnal Pengabdian Masyarakat, 2022)
One of the tasks in the tri dharma of higher education for a lecturer is to carry out community service activities. The purpose of this community service activity is to provide knowledge to the community directly through the training held. One of the training objects given to employees in Sei Mencirim Sunggal Village. The training provided is about creating and managing databases to make it easier to archive letters in the village. The database is an information system that functions to input and process data in a commercialized manner that can be used at any time by users of the system.